INTERCONNECTEDNESS OF LANGUAGE LEARNING PROGRESS WITH TEMPERAMENT TYPE - Mirsalikhova Robiya Timurovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article substantiates the need for a teacher to know the temperament of students, which allows him to better understand some of the features of their behavior, difficulties arising in educational activities, and their causes, and also makes it possible to vary the methods of educational actions. The specificity of the influence of students' temperament on their learning of a foreign language is revealed